Über die Fluoridaufnahme von Forellen bei Fütterung mit Krillmehlpellets - Tiews, K.; Manthey, Monika; Koops, H. (1981)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010